1992
DOI: 10.1016/s0950-3536(11)80048-x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular analysis of the t(15;17) translocation in acute promyelocytic leukaemia

Abstract: All rights reserved INFORMATION TO ALL USERS The quality of this reproduction is d e p e n d e n t upon the quality of the copy subm itted. In the unlikely e v e n t that the a u thor did not send a c o m p le te m anuscript and there are missing pages, these will be noted. Also, if m aterial had to be rem oved, a n o te will ind ica te the deletion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 226 publications
(275 reference statements)
0
3
0
Order By: Relevance
“…Acute promyelocytic leukemia (APL) is a unique subtype of acute myeloid leukemia (AML) 1 . Cytogenetically, APL is characterized by a chromosomal t(15;17) translocation, which results in production of the oncogenic PML/RARα fusion protein 2 , 3 . Intensive studies of APL pathogenesis have resulted in several breakthroughs in the treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Acute promyelocytic leukemia (APL) is a unique subtype of acute myeloid leukemia (AML) 1 . Cytogenetically, APL is characterized by a chromosomal t(15;17) translocation, which results in production of the oncogenic PML/RARα fusion protein 2 , 3 . Intensive studies of APL pathogenesis have resulted in several breakthroughs in the treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The fusion of the N-terminus of the PML, on chromosome 15, to the C-terminus of the RARA, on chromosome 17, explains APL pathogenesis in 95-98% of cases, resulting in the production of the biological hallmark of the disease: the PML/RARA rearrangement and the consequent oncogenic chimeric protein [5][6][7]. The prominent role of the rearrangement has been recently stressed by the updated 2016 WHO classification, which renamed this leukemia as "APL with PML-RARA" [8].…”
Section: Introductionmentioning
confidence: 99%
“…12 It has been proposed that PR␣ acts in a dominant-negative fashion to suppress the normal function of both PML and RAR␣. 13,14 Mouse models and cell culture experiments have demonstrated that PR␣ contributes to the leukemic phenotype mainly by inhibiting differentiation of hematopoietic progenitor cells.…”
Section: Introductionmentioning
confidence: 99%